2001
DOI: 10.1093/bja/87.3.507
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothorax: an unexpected complication after laparoscopic myomectomy

Abstract: We report a case of hydrothorax as a complication of laparoscopic myomectomy in an otherwise healthy woman. The most likely cause of the patient's hydrothorax was irrigation fluid moving from the peritoneal cavity into the pleural space via defects in the diaphragm. Anaesthesists and surgeons should consider hydrothorax as a potential complication in any patient undergoing laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Hydrothorax complicating peritoneal dialysis is also well reported 4 . The prevalence of hydrothorax in cases of liver cirrhosis and peritoneal dialysis is 6 and 2% respectively 6 . Over the period of 3 months, when these three cases underwent their surgery, a total of 49 cases of operative laparoscopy were carried out in our unit.…”
Section: Discussionmentioning
confidence: 81%
“…Hydrothorax complicating peritoneal dialysis is also well reported 4 . The prevalence of hydrothorax in cases of liver cirrhosis and peritoneal dialysis is 6 and 2% respectively 6 . Over the period of 3 months, when these three cases underwent their surgery, a total of 49 cases of operative laparoscopy were carried out in our unit.…”
Section: Discussionmentioning
confidence: 81%
“…In other cases, it was also reported that a hydrothorax occurred after gynecologic laparoscopical surgery [9,10]. A massive hydrothorax was produced during surgery, particularly at the right-sided chest.…”
Section: Discussionmentioning
confidence: 88%
“…This pathology is termed as porous diaphragm syndrome [3,4]. This may lead to transfer of gases or fluids into the thoracic cavity from abdomen [5]. The gases can also travel through the esophageal hiatus into the mediastinum and pleura [6].…”
Section: Discussionmentioning
confidence: 99%